PENINGKATAN KEMAMPUAN MENULIS PANTUN MELALUI METODE TTW (THINK, TALK, AND WRITE) SISWA KELAS IV SDN 1 PLATAR, TAHUNAN, JEPARA (Improving Capability in Writing Traditional Poetry through TTW Method (Think, Talk, and Talk) at the Students of Year IV, Pl (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2010)
The background of this research were that students’ capability in writing traditional poetry was still low, they were lack of being active, so that there were no optimal interactions between students and teacher or vice versa. The teacher always used conventional teaching method (teacher centered learning) in teaching process, so that it was necessary to apply TTW teaching method (think, talk, and write) on the Indonesian language subject, especially in the topic on writing traditional poetry. This was classroom action research covering the activities of planning, acting, observing, and reflecting. Those were done several times in cycles. This research was done by collaborating among all teachers of Platar 1 State Primary School, Tahunan Jepara. The research result showed that (1) average score for writing tradional poetry  was 64.27 at cycle 1. At the next cycle was 74.13, and at the last cycle to be 86.67. The next result was that the students’ activity observation score improve from cycle 1 up to cycle 3. at cycle 1 the average score was 69%, cycle 2 was 76%, and at cycle 3 was 87%. Observation score on teacher’s activity also improved on each cycle. At cycle 1, the average score on teacher’s activity was 68.75%, cycle 2 was 85.71%, and at cycle 3 improved to be 86.43%. The teacher had used TTW method at each step of teaching process (cycle 1 up to 3). TTW method consisted of think, meaning that the students payed attention to the reading and making the traditional poetry done by teacher. Talk here meant that the students did discussion under teacher’s guide, and the last was write, meaning  that they wrote traditional poetry individually or in groups. Based on the research result, it could be concluded that the use of TTW method was effective to improve students’ capability in writing traditional poetry for the students of year IV, Platar 1 State Primary School. Keywords: write, traditional poetry, think, talk, write